Implantable loop recorder migration: Case-based review and implications for clinical practice - Allam Harfoush (American Heart Journal Plus)
Introduction: Implantable loop recorders (ILRs) are vital for continuous rhythm monitoring; however, post-implantation migration can impair device function. ILR migration may range from minor positional shifts causing discomfort to severe displacement, potentially resulting in device malfunction or requiring surgical intervention. This review examines migration patterns to identify factors associated with ILR migration. Methods: A systematic literature search was conducted in PubMed, Cochrane Library, CINAHL, and EMBASE for case reports on ILR migration from inception to October 2024. Data on patient demographics, comorbidities, device models, implantation sites, detection times, and interventions were qualitatively synthesised to identify factors linked to migration. Results: Older age, female gender, and specific comorbidities emerged as migration risk factors. Device implantation angulation and depth were common contributors. Migration typically followed a posterior or inferior direction and was detected within 5–35 days, often presenting as loss of connection or continuous chest pain. Migration was also observed following patient manipulation of the device. Although migration is rare, cases requiring video-assisted thoracoscopic surgery (VATS) highlight the significant morbidity associated with this complication. Conclusion: Optimising implantation techniques and employing effective follow-up strategies can reduce the risk of migration and improve migration detection. Further studies with standardised reporting are needed to better understand this complication.